Profiling Non-motor Symptoms in Monogenic Parkinson’s Disease - Liu, Xinyao; Le, Weidong (Frontiers in Aging Neuroscience, 2020)
Parkinson's disease (PD) is the second most common neurodegenerative disease in elder population, pathologically characterized by the progressive loss of dopaminergic neurons in the substantia nigra. While the precise mechanisms underlying the pathogenesis of PD remain unknown, various genetic factors have been proved to be associated with PD. To date, at least 23 loci and 19 disease-causing genes for PD have been identified. Although monogenic (often familial) cases account for less than 5% of all PD patients, exploring the phenotypes of monogenic PD can help us understand the disease pathogenesis and progression. Primary motor symptoms are important for PD diagnosis but only detectable at a relatively late stage. Despite typical motor symptoms, various non-motor symptoms (NMS) including sensory complaints, mental disorders, autonomic dysfunction and sleep disturbances also have negative impacts on the quality of life in PD patients and pose major challenges for disease management. Moreover, NMS appears years or even decades before motor symptoms and have been recognized as important features of PD in premotor phase. Therefore, the profiling and characterization of NMS in monogenic PD may help establish early diagnostic marks and thereafter provide intervention at an early stage aiming to prevent disease development or delay disease progression. In this review, we summarized the characteristics, clinical phenotypes, especially the NMS of monogenic PD patients carrying mutations of SNCA, LRRK2, VPS35, Parkin, PINK1, DJ-1 and GBA. The clinical implications of this linkage between NMS and PD-related genes are also discussed.